TANGGUNG JAWAB KEKUATAN MENGIKAT KODE ETIK NOTARIS DALAM PEMBUATAN AKTA-AKTA NOTARIS DI WILAYAH KABUPATEN TANJUNG JABUNG BARAT - Nur Fauzia (Universitas Batanghari Jambi, 2016)
With the presence of the notary public code of conduct, then the Notary in performing tasks and authority as well as to make the deed must be accountable and to the provisions of the code of conduct. Thus, the notary public code of conduct binding on all things will be done by the Notary deeds in Office.Force of law Notary code of conduct mandatory also implemented by the Notary in the region of the Western Cape Jabung Regency in making the deed-notary deed of an act of law that occurred in the middle of the life of the community. But in reality, there are just the notary who made the deed is not in line with the provisions of the code of etiknya, which resulted in the existence of problems or disputes in the community caused the discharge or publication of the notary deed.Deviation of the acts committed by the notary deed in the making that can harm society can eliminate the responsibility of the force of law Notary code of conduct itself. However, it is not no action against a notary public in violation of the provisions of the code of conduct in the making of the notary deed, but the Notary may incur sanctions have also been set in the notary public code of ethics.Keyword : Code of ethics, the notary